Assistence for the Desa Cinta Statistik Agent in Pakatto Village Gowa Regency to Supporting the Acceleration of Satu Data Desa Indonesia - Anugra S. A. Dunggio; Subhan Muhammad; Nurhikmah; Nasria Eka Putri; Zakiyah Mar’ah; Rahmat H.S. (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Villages have a strategic role as sources of sectoral data to support evidence-based development planning. However, limited data literacy and statistical governance are still obstacles at the village level. This service activity aims to strengthen statistical data management through the Love Statistics Village Program (Desa Cantik) in Pakatto Village, Gowa Regency. Activity methods include mentoring, data collection and verification, and dissemination of village statistical output. The results of the activity show an increase in the quality and utilization of village data which is realized through the publication of statistics, infographics, thematic maps and village monographs.